Luke/acts and the end of history - Crabbe, Kylie (Zeitschrift für die neutestamentliche Wissenschaft und die Kunde der älteren Kirche, 2019)
Frontmatter -- Preface -- Contents -- Abbreviations -- Translations -- Chapter 1: Introduction -- Chapter 2: Genre, themes that transcend genre, and the approach of this study -- Chapter 3: The direction and shape of history -- Chapter 4: Determinism and divine guidance of history -- Chapter 5: Human responsibility and freedom -- Chapter 6: The present and the end of history -- Chapter 7: Conclusion -- Appendices -- Bibliography -- Index of ancient sources -- Index of modern authors -- Index of subjects